Short synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Pawar, Kailash P. (Tetrahedron Letters, 2013)
A convenient synthesis of (2S,3S)-3-hydroxypipecolic acid starting from cheap and abundant L-(+)-tartaric acid has been achieved. The strategy employs selective ester reduction and reductive lactamization as key steps. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reductive lactamization; Selective deprotection; Wittig reaction